دراسة وراثية لمطوافر البكتيرية المحممة لممركبات الفينولية - الياس, ميساء جاسب; حامد, دانية منعم; حمزة, صبحي جواد (Al-Nahrain Journal of Science, 2011)
were obtained from 55 soil`s sample and 10 bacterial isolates were obtained from water sample that contaminated with oil derivatives. These isolates were submitted to phenol and analine degradation. Five isolates were selected depending on their ability to degraded these compounds and identified as Pseudomonas aeruginosa A5